Trik or treat dora - Testa, Maggie; chikaswa, aka; fruchter, Jason (New yourk, USA Nickelodeon, 2010)
It's halloween, and dora's going triks-or-treating come along for a spook-teacher story with touch-and-feel cotumes on every page
"With costumes to touch and more"
12
Keywords: English stories